Description of Trischistoma abharensis n. sp. (Nematoda: Trischistomatidae) and first record of Tripylella intermedia (Bütschli, 1873) Brzeski & Winiszewska-Ślipinska, 1993 (Nematoda: Tripylidae) from Iran - Asghari, Ramezan; Eskandari, Ali; Maafi, Zahra Tanha; Zhao, Zeng Qi; Álvarez-Ortega, Sergio; Nadirkhanloo, Majid (Zootaxa, 2015)
Two populations of the genera Trischistoma and Tripylella were recovered from the rhizosphere of grapevines and mosses growing on alder trees in Zanjan and Guilan provinces, respectively, Iran. The nematodes were identified as Trischistoma abharensis n. sp. and Tripylella intermedia, respectively. Trischistoma abharensis n. sp. is characterized by having females with body length 1069–1322 μm, presence of sparse somatic setae on the sublateral body, absence of ventromedian cervical setae, a distinct dorsal tooth directed anteriorly, absence of post-vulval uterine sac, and tail with one pair of subdorsal caudal setae. Males were not found. Tripylella intermedia is characterised by having females with body length 905–990 μm, annulated cuticle, stoma with two chambers: with dorsal tooth lying in posterior buccal chamber, and one large subventral and one small subventral tooth, respectively lying in posterior and anterior buccal chambers, cardiac glands large, composed of six fused cells, and tail 121–155 μm long, ventrally bent, anterior half broad, then suddenly narrowing, with posterior half tapered narrowly and cylindrically. The phylogenetic relationships of both species were analysed using sequences of the partial small subunit (SSU) and D2/D3 expansion segments of large subunit (partial LSU) of ribosomal RNA genes and are discussed.